The trouble with do-gooders: the example of suicide. - Savulescu, J (1997)
This paper describes the concept of a do-gooder: a person who does unwanted good. It illustrates why doing-good is a problem and argues that patients should not be compelled to do what is best. It shows the ways in which doctors covertly do-good and offers a critique of these. The discussion focuses on the example of the treatment of patients who attempt suicide.